Characteristic Features of Ethnic Labor Migration in the Krasnoyarsk Krai (Central Siberia, Russia) - Koptseva, Natalia P.; Zamarayeva, Yulia S.; Kirko, Vladimir I. (International Journal of Economics and Financial Issues, 2015)
This research is devoted to the analysis of some aspects of ethnic labor mobility in Krasnoyarsk Krai. The main method of research is a quantitative survey, including the interpretation of the quantitative results. Currently, Krasnoyarsk Krai (Central Siberia, Russia) is a zone of active ethnic labor mobility. The majority of the ethnic migrant workers are from Central Asia (Tajikistan, Uzbekistan, Kyrgyzstan). Ethnic labor mobility from Armenia and Azerbaijan is decreasing. The hosts, the residents of the Krasnoyarsk Krai, are experiencing a range of phobias towards the labor immigrants (xenophobia and migrant-phobia). For the harmonization of relationships between migrants and the hosts, preventative measures should be taken to prevent possible confl icts, including constant monitoring of the situation. The study shows that students and youth of the Siberian Federal University have a positive attitude toward people who are engaged in labor mobility. Political management should take the complex structure of the host into the account and be ready to regulate diffi cult intercultural relationships between the people of Krasnoyarsk Krai and the people who come there from Central Asia and other countries. Keywords: Krasnoyarsk Krai, Ethnic Labor Mobility, Strategies of Acculturation, Cultural Integration JEL Classifications: J15, J61, R12, Z13